Analisis Pengaruh Electronic Word Of Mouth Dan Citra Destinasi Terhadap Minat Berkunjung (Studi Kasus Ladaya Kutai Kartanegara) - Dilla, Dilla; Raharjo, Sugeng; Suprapto, Heru (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: The purpose of this study was to determine the effect of electronic word of mouth and destination image variables on visiting interest either partially or simultaneously. Besides that, to find out the variables that have the most dominant influence on visiting interest. This research is a quantitative study using multiple regression analysis techniques with the help of the SPSS 20.0 for Window program, using a questionnaire with a sample of 91 (ninety one) from a population of 910 (nine hundred and ten) visitors to Ladaya. The results showed that the variable electronic word of mouth (X1) and destination image (X2) had a simultaneous and partial effect on visiting interest (Y). From the t test, it can be seen that the electronic word of mouth (X1) variable has a greater t-count coefficient than the destination image (4.631>3.881). Thus, it can be concluded that the electronic word of mouth (X1) variable has the most dominant influence on interest in visiting Ladaya Kutai Kartanegara. Keywords: Electronic Word Of Mouth, Destination Image, Visiting Interest